2021
DOI: 10.3390/plants10112254
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cellular Redox Status and Antioxidant Defense System after Synergistic Application of Zinc Oxide Nanoparticles and Salicylic Acid in Rice (Oryza sativa) Plant under Arsenic Stress

Abstract: The objective of this research was to determine the effect of zinc oxide nanoparticles (ZnONPs) and/or salicylic acid (SA) under arsenic (As) stress on rice (Oryza sativa). ZnONPs are analyzed for various techniques viz., X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). All of these tests established that ZnONPs are pure with no internal defects, and can be potentially used in plant applications. Hence, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Some scientists have identified adverse effects on plants (Minkina et al, 2020;Usman et al, 2020;Zoufan et al, 2020), animals (Rajput et al, 2017;Rajput et al, 2018), and soil characteristics . At the same time, the other researchers confirmed the absence of any adverse effects (Faizan et al, 2021;Samarajeewa et al, 2017) or even note a positive effect (Acharya et al, 2020;Faizan et al, 2020;Shekhawat et al, 2021). Nanoparticles entering the soil are distributed differently depending on soil fertility, structure, and composition.…”
Section: Introductionmentioning
confidence: 74%
“…Some scientists have identified adverse effects on plants (Minkina et al, 2020;Usman et al, 2020;Zoufan et al, 2020), animals (Rajput et al, 2017;Rajput et al, 2018), and soil characteristics . At the same time, the other researchers confirmed the absence of any adverse effects (Faizan et al, 2021;Samarajeewa et al, 2017) or even note a positive effect (Acharya et al, 2020;Faizan et al, 2020;Shekhawat et al, 2021). Nanoparticles entering the soil are distributed differently depending on soil fertility, structure, and composition.…”
Section: Introductionmentioning
confidence: 74%
“…Previous studies have shown that ZnO NPs dissociate, releasing Zn ions into the medium [56], and according to Alloway [57], Zn decreases the uptake of Cu 2+ because both metals are taken up by the same transporter. Faizan et al [58] reported an increase in mineral content (N, K + , Zn 2+ , Mn 2+ , and Fe 2+ ) due to the application of ZnO NPs.…”
Section: Effect Of Zno Nps On Mineral Contentmentioning
confidence: 99%
“…Conversely, there were no statistical differences in the interaction of grafting with ZnO NPs applications, as they showed lower contents of soluble solids compared to the control plants. Faizan et al [58] reported that the use of ZnO NPs is one of the new strategies to improve the growth and performance of plants under stress by trace metals.…”
Section: Interactive Effects Of Grafting and Zno Nps On Fruit Qualitymentioning
confidence: 99%
“…The use of NPs with bioremediation approaches may result in a lot of benefits as these particles are small (1–100 nm) with a larger surface area and reactivity [ 10 ]. The broad range of studies indicated that the foliar use of NPs alleviates metal-pollutant toxicity and enhances plant growth, resulting in a high accumulation of elemental toxic content in plant tissues [ 11 , 12 , 13 ]. The degree of contamination, the bioavailability, and the accumulation of metals by the plants are decisive for the efficiency of nano-phytoremediation as a way of removing heavy metals (HMs) from contaminated sites [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%